Clinical Association Between Triglyceride-to-HDL Cholesterol Ratio and C-Reactive Protein in Adults with Central Obesity - Meita Hendrianingtyas; Edward Kurnia Setiawan Limijadi; Villa Sekar Cita; Banundari Rahmawati; Annta Kern Nugrohowati (Molecular and Cellular Biomedical Sciences, 2026)
Background: Central obesity contributes to insulin resistance, atherogenic dyslipidemia, and chronic low-grade inflammation, increasing cardiometabolic risk. The triglyceride-to-HDL cholesterol (TG/HDL-C) ratio is a simple marker of dyslipidemia and insulin resistance, while C-reactive protein (CRP) reflects systemic inflammation. However, evidence linking these indicators remains inconsistent, especially in Asian populations. This study aims to assess the association between TG/HDL-C ratio and CRP levels in adults with central obesity.Materials and methods: A cross-sectional study was conducted among 80 adults with central obesity at Diponegoro National Hospital, Indonesia. Fasting lipid profiles, including triglycerides and HDL cholesterol, and CRP were measured using standard biochemical methods. The TG/HDL-C ratio was calculated, and its association with CRP levels was analyzed using the chi-square test (p<0.05).Results: Among the participants, 57.5% had an elevated TG/HDL-C ratio (≥2.5), whereas elevated CRP levels (≥3 mg/L) were observed in only 6.25% of subjects. Statistical analysis showed no significant association between TG/HDL-C ratio and CRP levels (p=0.90).Conclusion: Most adults with central obesity had an elevated TG/HDL-C ratio, while elevated CRP levels were relatively uncommon. However, no significant association was found between TG/HDL-C ratio and CRP. These findings suggest that dyslipidemia and systemic inflammation may occur at different stages of metabolic dysfunction. Further longitudinal studies with larger sample sizes are needed to clarify this relationshi.Keywords: central obesity, TG/HDL-C ratio, c-reactive protein, inflammation